84.4k views
5 votes
(-5y^2-9y-4)-(-2y^2-y+8)

User Michael
by
4.4k points

2 Answers

11 votes

Answer:


-3y^2-8y-12

Explanation:

Simplify each term.


-5y^2-9y-4+2y^2+y-8

Simplify by adding terms.


-3y^2-8y-12

hope this helps :)

User Mamal
by
5.1k points
6 votes

Answer:

−3y2−8y−12

Explanation:

Let's simplify step-by-step.

−5y2−9y−4−(−2y2−y+8)

Distribute the Negative Sign:

=−5y2−9y−4+−1(−2y2−y+8)

=−5y2+−9y+−4+−1(−2y2)+−1(−y)+(−1)(8)

=−5y2+−9y+−4+2y2+y+−8

Combine Like Terms:

=−5y2+−9y+−4+2y2+y+−8

=(−5y2+2y2)+(−9y+y)+(−4+−8)

=−3y2+−8y+−12

User Joel Hoelting
by
4.7k points